EP408 Usefulness of evaluating lymphatic and venous vessel invasion separately in postoperative cervical adenocarcinoma. (1st November 2019) - Taira, Y; Shimoji, Y; Nakasone, T; Arakaki, Y; Nakamoto, T; Ooyama, T; Kudaka, W; Aoki, Y
Abstract : Introduction/Background: Surgical treatment of cervical adenocarcinoma is expected to improve prognosis since the cancer is less responsive to radio- and chemotherapy than cervical squamous cell carcinoma. Attempts are made to predict recurrence patterns and prognosis using surgical specimens, including evaluation of vascular invasion. In other types of cancer, such as gastric, colon and breast cancer, it is known that evaluating lymphatic and venous vessel invasion separately helps predict prognosis and recurrence sites, such as lymph node metastasis and distant metastasis. In this study, we aimed to determine the significance of evaluating lymphatic and venous vessel invasion separately in postoperative cervical adenocarcinoma. Methodology: We retrospectively examined the medical records of 108 patients who were diagnosed with cervical adenocarcinoma or adenosquamous carcinoma and underwent abdominal radical hysterectomy at University of the Ryukyus Hospital from January 1993 to April 2017. The patients were separately evaluated for lymphatic and venous vessel invasion using immunohistochemical staining with D2-40 and haematoxylin and eosin Victoria blue double staining. Results: Lymphatic and/or venous invasions were observed in 42 (38.9%) patients, including 66 ly(−)/v(−) (61.1%), 7 ly(−)/v(+) (6.5%), 24 ly(+)/v(−) (22.2%) and 11 ly(+)/v(+) (10.2%) patients. In multivariate analysis of risk factors for distant recurrence, stage (IB2 or higher) (odds ratio=6.21, p=0.020) and venous invasion (odds ratio=9.29, p=0.0047) were considered significant. In multivariate analysis of predictive factors for poor prognosis, stage (IB2 or higher) (hazard ratio=5.33, p=0.0315) and pelvic lymph node metastasis (hazard ratio=7.81, p=0.0142) were considered significant. Conclusion: In radical hysterectomy for cervical adenocarcinoma, venous vessel invasion was found to be a risk factor for distant organ recurrence, but separately evaluating lymphatic and venous vessel invasion is not useful for predicting prognosis. Disclosure: Nothing to disclose.